2014
DOI: 10.1016/j.resinv.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the clinical effects of pirfenidone on idiopathic pulmonary fibrosis

Abstract: a b s t r a c tBackground: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease with a poor prognosis. Recently, pirfenidone was reported to slow the rate of decline in vital capacity and improve progression-free survival in IPF. The purpose of this study was to clarify the factors that predicted a good response to pirfenidone, as well as its adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 28 publications
1
21
0
5
Order By: Relevance
“…In addition to long-term observational studies, a number of recent single-centre studies have been published reporting the efficacy and tolerability of pirfenidone in a real-world setting (table 3) [13][14][15][16][17][18][19][20]. Generally, these single-centre observational studies demonstrate that in daily clinical practice the tolerability of pirfenidone is comparable to the literature with a positive effect in terms of clinical efficacy in the majority of patients treated, particularly regarding disease stabilisation and prevention of pulmonary function decline.…”
Section: Single-centre Real-world Experience With Pirfenidonementioning
confidence: 99%
“…In addition to long-term observational studies, a number of recent single-centre studies have been published reporting the efficacy and tolerability of pirfenidone in a real-world setting (table 3) [13][14][15][16][17][18][19][20]. Generally, these single-centre observational studies demonstrate that in daily clinical practice the tolerability of pirfenidone is comparable to the literature with a positive effect in terms of clinical efficacy in the majority of patients treated, particularly regarding disease stabilisation and prevention of pulmonary function decline.…”
Section: Single-centre Real-world Experience With Pirfenidonementioning
confidence: 99%
“…The study by ARAI et al [20] is also from Japan. This study investigated possible predictors of response to therapy with pirfenidone in 41 patients with IPF: diagnosis by a surgical lung biopsy and milder disease were predictors of good, short-term responsiveness.…”
Section: Real-life Clinical Experience With Pirfenidone In Ipfmentioning
confidence: 99%
“…In 10 patients with milder disease (out of 21 patients evaluated), the change in vital capacity (VC) 3 and 12 months before and 3 and 6 months after initiation of pirfenidone therapy was significantly decreased ( p=0.0039), although this was not the case in the other, more severe patients (n=11). Additionally, ARAI et al [20] suggested that patients taking acid-secretion inhibitors, including proton pump inhibitors and histamine H2-receptor antagonists, showed less anorexia, less nausea or both.…”
Section: Real-life Clinical Experience With Pirfenidone In Ipfmentioning
confidence: 99%
“…2011-2014: long-term and real-world experience in the treatment of IPF with pirfenidone Since the approval of pirfenidone in 2011 by the EMA, important data on the use of pirfenidone from clinical studies, long-term observational studies and real-world practice has been accumulated, demonstrating that pirfenidone significantly reduces forced vital capacity (FVC) decline and slows disease progression in IPF [22][23][24][25][26][27][28][29][30]. These longer term studies also showed that pirfenidone is generally well tolerated.…”
Section: Introductionmentioning
confidence: 99%